Analisis Bibliometrik Bidang Matematika dan Ilmu Pengetahuan Alam - Catur Dedek Khadijah; Tessa Simahate; Donni Yudha Prawira; Cut Lidya Mutia; Puspita Winda Misa (Mahesa Research Center, 2023)
The purpose of this research is to determine the results of the theses by students at the Faculty of Mathematics and Natural Sciences from 2018-2020, and their suitability which includes: the field of science that is being examined, boring topics that are no longer in demand, and Trends in the distribution of topics growing based on the Dewey Decimal Classification standard. This is a quantitative and qualitative research carried out to determine the distribution of thesis topics as the basis for developing the roadmap of each study program at the Faculty of Mathematics and Natural Sciences. Data were collected from the repository and tabulated data tabulations of the summary of results. The results indicate that the number of undergraduate thesis at the Faculty of Mathematics and Natural Sciences from 2018 to 2020 is 2.416 titles. The mapping of fields of science based on Dewey Decimal Classification showed the topics of each study program. Based on the data, the in-demand topics for each study program are Chemical equilibrium; Miscellaneous topics in physical chemistry; Prescription Filling; Education, Research, Related Topics; Physical Chemistry; Kinematics; Descriptive statistics, multivariate analysis; analysis of variance and covariance and Mathematical models (mathematical simulation).